Key Characteristics of Employment Regulation in the Middle East and North Africa - Angel-Urdinola, Diego F.; Kuddo, Arvo (World Bank, Washington, DC, 2017)
This note provides a general background of the main features of labor regulation in the Middle East and North Africa (MENA) and benchmarks them against international best practices. The note compiles information on available labor laws and other legal acts concerning employment protection regulation. Within the broader scope of labor regulation, and in order to assure regional comparability, information collected focuses on key issues in the labor law associated with commencing or terminating employment and during the period of employment (including maternity benefits). The main sources the data are the World Bank doing business 2010 and International Labour Organisation (ILO) databank. This note is a tool to provide policymakers and international organizations with a regional diagnose of how labor regulation affects labor market outcomes in MENA and inform client governments about strategic approaches to employment creation through labor policy and reform. This activity comes as a response to regional priorities in the context of the Arab World Initiative (AWI). One of the six strategic themes of the AWI focuses explicitly on employment creation as a top priority. Part of the World Bank's mandate under the AWI is to inform client governments about strategic approaches to employment creation through labor policy and reform.